Polymeric micelles loaded with carfilzomib increase tolerability in a humanized bone marrow-like scaffold mouse model - Aida Varela-Moreira; Demian van Straten; Heleen F. van Leur; Ruud W.J. Ruiter; Anil K. Deshantri; Wim E. Hennink; Marcel H.A.M. Fens; Richard W.J. Groen; Raymond M. Schiffelers (Elsevier, 2020)
Carfilzomib-loaded polymeric micelles (CFZ-PM) based on poly(ethylene glycol)-b-poly(N-2-benzoyloxypropyl methacrylamide) (mPEG-b-p(HPMA-Bz)) were prepared with the aim to improve the maximum tolerated dose of carfilzomib in a "humanized" bone marrow-like scaffold model. For this, CFZ-PM were prepared and characterized for their size, carfilzomib loading and cytotoxicity towards multiple myeloma cells. Further, circulation and tumor & tissue distribution of fluorescently labeled micelles were determined. Tolerability of CFZ-PM versus the clinical approved formulation - Kyprolis® - was assessed. CFZ-PM presented small diameter below 55 nm and low PDI < 0.1. Cy7-labeled micelles circulated for extended periods of time with over 80% of injected dose in circulation at 24 h after intravenous injection and 1.3% of the injected dose of Cy7-labeled micelles accumulated in myeloma tumor-bearing scaffolds. Importantly, CFZ-PM were well tolerated whereas Kyprolis® showed adverse effects. Kyprolis® dosed at the maximum tolerated dose, as well as CFZ-PM, did not show therapeutic benefit, while multiple myeloma cells showed sensitivity in vitro, underlining the importance of the bone marrow crosstalk in testing novel formulations. Overall, this work indicates that PM are potential drug carriers of carfilzomib.